High‐Throughput Electrical Potential Depth‐Profiling in Air. Issue 16 (29th June 2017) - Rietwyk, Kevin J.; Keller, David A.; Majhi, Koushik; Ginsburg, Adam; Priel, Maayan; Barad, Hannah‐Noa; Anderson, Assaf Y.; Zaban, Arie
Abstract : The operation of thin‐film electronic devices is dictated by the band alignment at the interfaces of the various layers. While a number of methods for measuring the depth profile of the electrical potential at interfaces have emerged, these are typically arduous to perform and involve the use of ultrahigh vacuum, complicated sample preparation, and/or suffer from poor resolution. Here a method to directly map the depth profile of the electrical potential is presented at an interface in air by growing a sample with an intentional thickness gradient and correlating the surface potential, measured using (macroscale) scanning Kelvin probe, to the thickness at each point. The approach is nondestructive and rapid, is ideal for large substrates and films grown with an inherent thickness gradient. It enjoys very high depth (2 nm) and energy resolution (5 meV), comparable to other methods. In this work, the method is developed and demonstrated on a TiO2 |Co3 O4 all‐oxide junction and a depletion width of only 8.6 ± 3.8 nm in the Co3 O4 layer is shown. Abstract : A novel methodology for depth profiling the electrical potential at interfaces that can be performed in air is presented. The approach is nondestructive, rapid, and enjoys high depth and energy resolution. In this work the method is developed and demonstated on FTO|TiO2 |Co3 O4 all‐oxide junctions and a depletion width of only 8.6 ± 3.8 nm in the Co3 O4 layer is shown.